Step 1: Decide on the variable to be eliminated | The variable x can be eliminated by adding the equations if the coefficient of x in equation (1) is changed to -6x. |
Step 2: Eliminate the variable by suitably multiplying the equations and adding them. In the above problem the first equation is multiplied by -2. | Equation(1)*(-2) -6x – 8y = +2 6x – 2y = 3 -------------------- -10 y = 5 y = 5 / -10 ( dividing both sides by -10) y = - ½ |
Step 3: Plug in the value of y found in any one of the given equations and solve for x | Plugging y = `-1/2` in equation (1) 3x + 4( -1/2) = -1 3x + (-2) = -1 3x = +1 Transposing -2 to the right side x = `1/3` Dividing by 3 and simplifying |
Check: Plug the values of x and y found in equation (2) and check whether the equation Is satisfied. | 6 x (1/3) - 2 x (-1/2) = 3 2 + 1 = 3 The equation is satisfied. |